2011
DOI: 10.3109/07853890.2011.573805
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and physical properties of regenerative medicine materials controlling stem cell fate

Abstract: Regenerative medicine is a multidisciplinary field utilizing the potential of stem cells and the regenerative capability of the body to restore, maintain, or enhance tissue and organ functions. Stem cells are unspecialized cells that can self-renew but also differentiate into several somatic cells when subjected the appropriate environmental cues. The ability to reliably direct stem cell fate would provide tremendous potential for basic research and clinical therapies. Proper tissue function and regeneration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 144 publications
0
45
0
Order By: Relevance
“…Repeated mechanical stress on the membrane during each movement step induces trauma and hypoxic conditions leading to proliferation of fibroblasts that synthesize an abundant extracellular matrix to adapt to the stresses and strains around the implant. It has been shown that the mechanical environment can induce the differentiation of mesenchymal stem cells via up- and/or down-regulation of mechano-sensitive genes and in this way biomechanical loads can influence tissue differentiation resulting in excessive formation of fibrous tissue [119121]. Interestingly, macrophages significantly increase their expression of TNF-α, IL-1β and IL-6 when they are treated conjointly with polyethylene particles and pressure [122, 123].…”
Section: Integral Theory Of Periprosthetic Osteolysis Around Tkamentioning
confidence: 99%
“…Repeated mechanical stress on the membrane during each movement step induces trauma and hypoxic conditions leading to proliferation of fibroblasts that synthesize an abundant extracellular matrix to adapt to the stresses and strains around the implant. It has been shown that the mechanical environment can induce the differentiation of mesenchymal stem cells via up- and/or down-regulation of mechano-sensitive genes and in this way biomechanical loads can influence tissue differentiation resulting in excessive formation of fibrous tissue [119121]. Interestingly, macrophages significantly increase their expression of TNF-α, IL-1β and IL-6 when they are treated conjointly with polyethylene particles and pressure [122, 123].…”
Section: Integral Theory Of Periprosthetic Osteolysis Around Tkamentioning
confidence: 99%
“…Because physical properties of materials participate in the control of the stem cell fate,8 we hypothesized that the pillars on cell culture substrate enable cell growth in layers and the formation of 3D tissue structures instead of planar monolayer growth. Extension of the cells growing on the top of one pillar perhaps to the top of one or more other pillars increases internal cytoskeletal tension and regulates the shape of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…The first one is correlated with the possibility of obtaining, in-vitro, developed vascular tissue [107,108]. In second instance, once a pseudo-physiological angiogenesis is achieved, the ambitious aim is to create engineered whole organs [109].…”
Section: • Mechanical Strengthmentioning
confidence: 99%